2020
DOI: 10.1007/s10658-020-02163-x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of bacteria from different species of Pectobacteriaceae on seed potato plantations in Poland

Abstract: Bacteria from the genera Dickeya and Pectobacterium, the causative agents of soft rot and blackleg, trigger significant economic losses in potato production worldwide. Efficient struggle with these phytopathogens is highly challenging taking into consideration the lack of available control procedures. As only preventive measures are accessible, we decided to provide insight into the soft rot Pectobacteriaceae (SRP) present in Poland. During the growing seasons of 2013 and 2014, altogether 531 potato plants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…Three of these strains cluster with Pectobacterium, the other genus grouping pectinolytic bacteria commonly involved in potato blackleg disease. These include two strains belonging to P. versatile, a species recently described to have a very broad host range [26] and one strain belonging to P. parmentieri, another recently described species that was, however, present in potatoes in Poland from the 1990s [27,28]. More unexpectedly, two strains closely cluster with Rahnella aquatilis, a gammaproteobacterium whose genus members have been isolated from soil, freshwater and food, but also clinical samples [29].…”
Section: Diversity Of the Pectinolytic Dickeya Isolated In Switzerlandmentioning
confidence: 97%
See 1 more Smart Citation
“…Three of these strains cluster with Pectobacterium, the other genus grouping pectinolytic bacteria commonly involved in potato blackleg disease. These include two strains belonging to P. versatile, a species recently described to have a very broad host range [26] and one strain belonging to P. parmentieri, another recently described species that was, however, present in potatoes in Poland from the 1990s [27,28]. More unexpectedly, two strains closely cluster with Rahnella aquatilis, a gammaproteobacterium whose genus members have been isolated from soil, freshwater and food, but also clinical samples [29].…”
Section: Diversity Of the Pectinolytic Dickeya Isolated In Switzerlandmentioning
confidence: 97%
“…Average nucleotide identity (ANI) analysis revealed that these six strains are highly similar with ANI percentage between them, ranging from 99.96 to 100% with a high percentage of all compared genomes being successfully aligned (99.03 to 99.99%). As already described [28], we refined this analysis by mapping the Illumina reads of the four Swiss genomes to the 3337 complete genome, allowing us to identify SNPs and InDels variations. The four Swiss strains only exhibit 53 to 94 SNPs/InDels, among which 49 are common to the four Swiss strains, indicating they are specific to the 3337 genome (Table 3).…”
Section: Genomic Analysis Of the Earlymentioning
confidence: 99%
“…It should be also highlighted that most of the previously published data describe the interaction between Arabidopsis plants and D. dadantii 3937. According to our best knowledge D. solani , which is an important plant pathogenic bacterium causing a loss in potato yield in Europe [ 34 , 51 , 52 ] was not tested before with a model plant Arabidopsis. Moreover, recent results show that D. solani strains cause severe disease symptoms in temperate climates, and are more aggressive than other blackleg-causing bacteria from genus Dickeya and Pectobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this genus joined the newly established Pectobacteriaceae family [ 2 ] due to the fact of their genomic characteristics and their ability to produce pectinolytic enzymes. These bacteria cause disease symptoms of blackleg on potato plants and soft rot on potato tubers and other vegetables, e.g., tomatoes, peppers, chicory, and ornamental plants [ 3 , 4 , 5 ]. The virulence of these pathogens results from the production of large quantities of plant-cell-wall-degrading enzymes (PCWDEs), i.e., pectinases, cellulases, and proteases that are secreted outside bacterial cells and allow for efficient maceration of plant tissue [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has been monitoring the occurrence of pectinolytic bacteria on seed potato plantations in Poland since 1996 [ 5 ]. The members of Pectobacteriaceae were also detected in some of the tested waterways in our country [ 36 ].…”
Section: Introductionmentioning
confidence: 99%